1994
DOI: 10.1183/09031936.94.07030504
|View full text |Cite
|
Sign up to set email alerts
|

Patient compliance with inhaled medication: does combining beta-agonists with corticosteroids improve compliance?

Abstract: P Pa at ti ie en nt t c co om mp pl li ia an nc ce e w wi it th h i in nh ha al le ed d m me ed di ic ca at ti io on n: : D Do oe es s c co om mb bi in ni in ng g b be et ta a--a ag go on ni is st ts s w wi it th h c co or rt ti ic co os st te er ro oi id ds s i im mp pr ro ov ve e c co om mp pl li ia an nc ce e? ? In an open, multicentre, parallel group study 102 asthmatic patients were randomly divided into two groups, either receiving the two drugs in separate Turbuhalers or combined into one Turbuhaler. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
9

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 13 publications
3
48
0
9
Order By: Relevance
“…Study results 16,30,[34][35][36][37][38][39] are shown in Table II. Some of these studies have been summarized previously.…”
Section: Adherence To Oral Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Study results 16,30,[34][35][36][37][38][39] are shown in Table II. Some of these studies have been summarized previously.…”
Section: Adherence To Oral Therapymentioning
confidence: 99%
“…Bosley et al 39 compared compliance with inhaled budesonide, terbutaline, and the 2 dry combinations in the Turbuhaler. In this open-label, multicenter study, 102 asthmatic patients were given the 2 drugs in separate Turbuhalers or combined in one.…”
Section: Dry Powder Inhalersmentioning
confidence: 99%
“…Compliance to inhaled corticosteroid therapy in asthma has been reported to be 30±70% [25,26]. How much this contributes to poor asthma control is not known.…”
Section: Patient Compliance and Supervisionmentioning
confidence: 99%
“…Therefore, the Global Initiative for Asthma (GINA) stated that follow-up consultations including assessment of patients' medication adherence and evaluation of inhaler device technique should occur at regular intervals (7). Currently, a variety of methods exist to assess adherence including medication counting (8,9), diaries, electronic monitors (10,11), questionnaires (12)(13)(14), and analysis of pharmacy claims databases (15)(16)(17). Some simple selfreported adherence questionnaires have been previously studied (12,18,19).…”
Section: Introductionmentioning
confidence: 99%